Development of a S/w System for Relative Positioning Using GPS Carrier Phase - Yong-Won Ahn; Chun-Hwey Kim; Pil-Ho Park; Jong-Uk Park; Jeong-Ho Jo (Journal of Astronomy and Space Sciences, 1997)
We developed a GPS phase data processing S/W system which calculates baseline vectors and distances between two points located in the surface of the Earth. For this development a Double-Difference method and L1 carrier phase data from GPS(Global Positioning System) were used. This S/W system consists of four main parts : satellite position calculation, Single-Difference equation, Double-Difference equation, and correlation. To verify our S/W, we fixed KAO(N36.37, E127.37, H77.61m), one of the International GPS Services for Geodynamics, which is located at Tae-Jon, and we measured baseline vectors and relative distances with data from observations at approximate baseline distances of 2.7, 42.1, 81.1, 146.6km. Then we compared the vectors and distances with the data which we obtained from the GPSurvery S/W system, with the L1/L2 ION-Free method and broadcast ephemeris. From the comparison of the vectors and distances with the data from the GPSurvey S/W system, we found baseline vectors X, Y, Z and baseline distances matched well within the extent of 50cm and 10cm, respectively.